Flexural behaviour of steel hollow sections filled with concrete that contains OPBC as coarse aggregate - Javed, Muhammad Faisal; Ramli Sulong, Nor Hafizah; Memon, Shazim Ali; Rehman, Sardar Kashif-Ur; Khan, Niaz Bahadur (Elsevier, 2018)
Oil-palm-boiler clinker (OPBC) is an agricultural waste from the palm oil industry and is considered a serious threat to the environment. Moreover, the high consumption of concrete as a construction material results in a continuous demand for natural aggregates, thereby negatively affecting the environment. Thus, channeling OPBC waste materials into the concrete industry aids in promoting the use of a sustainable and lightweight member. This research presents a novel sustainable composite beam that uses an OPBC as a replacement of the natural coarse aggregate. Flexural behaviour of steel tubes infilled with conventional and OPBC concretes were investigated. The results showed that the ductility, flexural stiffness and structural efficiency were higher in the OPBC concrete filled steel tube (CFST) than conventional CFST by 15%, 12% and 20%, respectively. Furthermore, in comparison to conventional CFST, the 10% less self-weight in OPBC CFST will significantly reduce the construction cost of the material. Conclusively, the utilisation of OPBC as infill material for CFSTs will solve disposal problem, preserve natural resources, reduce environmental pollution and will make the structural system sustainable.